I will never not ever eat a tomato - Child, Lauren (Cambridge, Mass. Candlewick Press, 2003)
A fussy eater decides to sample the carrots after her brother convinces her that they are really orange twiglets from Jupiter.
Keywords: Food habits -- Fiction; Brothers and sisters -- Fiction